Scaffolding Self‐Correction During Oral Reading. (24th January 2020) - Johnson, Tracy; Mikita, Clara; Rodgers, Emily; D'Agostino, Jerome V.
Abstract: Recent research has demonstrated that self‐correction is particularly important for beginning and struggling readers; readers who self‐correct more make progress more quickly. The authors describe findings from that research, outline how self‐correcting behavior might vary, and provide suggestions for how students' self‐corrections can inform scaffolded instruction.